Kinetic and stoichiometric parameters estimation in a nitrifying bubble column through ‘‘in-situ’’ pulse respirometry - Ordaz, Alberto (2008)
This article proposes a simple "in-situ" pulse respirometric method for the estimation of four important kinetic and stoichiometric parameters. The method is validated in a suspended biomass nitrifying reactor for the determination of (i) maximum oxygen uptake rate (OURexmax), (ii) oxidation yield (fE), (iii) biomass growth yield (fS), and (iv) affinity constant (KS). OURexmax and fE were directly obtained from respirograms. In the presented case study, a minimum substrate pulse of 10 mgNH4+-NL-1 was necessary to determine OURexmax which was 61.15 ± 4.09 mgO2 L-1 h-1 (5 repetitions). A linear correlation (r2 = 0.93) obtained between OURexmax and the biomass concentration in the reactor suggests that biomass concentration can be estimated from respirometric experiments. The substrate oxidation yield, fE, was determined along 60 days of continuous operation with an average error of 5.6%. The biomass growth yield was indirectly estimated from the substrate oxidation yield fE. The average obtained value (0.10 ± 0.04 mgCOD mg-1COD) was in accordance with the fS estimation by the traditional COD mass balance method under steady-state conditions (0.09 ± 0.01). The affinity constant KS was indirectly estimated after fitting the ascending part of the respirogram to a theoretical model. An average value of 0.48 ± 0.08 mgNH4+-NL-1 was obtained, which is in the range of affinity constants reported in the literature for the nitrification process (0.16-2 mgNH4+-NL-1).